Acute neurobehavioural effects of toluene. Issue 7 (July 1989) - Echeverria, D; Fine, L; Langolf, G; Schork, A; Sampaio, C
Abstract : An acute inhalation chamber study of 42 college students was performed to investigate the relation between exposure to 0, 75, and 150 ppm of toluene and changes in central nervous system function and symptoms. Paid subjects were exposed for seven hours over three days. Verbal and visual short term memory (Sternberg, digit span, Benton, pattern memory); perception (pattern recognition); psychomotor skill (simple reaction time, continuous performance, digit symbol, hand-eye coordination, finger tapping, and critical tracking); manual dexterity (one hole); mood (profile of mood scales (POMS]; fatigue (fatigue checklist); and verbal ability were evaluated at 0800, 1200, and 1600 hours. Voluntary symptoms and observations of sleep were collected daily. An analysis of variance and test for trend was performed on the difference and score for each concentration reflecting an eight hour workday where each subject was their own control. A 3 x 3 Latin square study design evaluated toluene effects simultaneously, controlling for learning across the three days and the solvent order. Intersubject variation in solvent uptake was monitored in breath and urine. A 5-10% decrement in performance was considered significant if it was consistent with a linear trend at p less than 0.05. Adverse performance at 150 ppm toluene was found at 6.0% for digit span, 12.1% for pattern recognition (latency), 5.0% for pattern memory (number correct), 6.5% for one hole, and 3.0% for critical tracking. The number of headaches and eye irritation also increased in a dose response manner. The greatest effect was found for an increasing number of observations of sleep. Overall, no clear pattern of neurobehavioural effects was found consistent with the type 1 central nervous system as classified by the World Health Organisation. Subtle acute effects, however, were found just below and above the ACGIH TLV of 100 ppm toluene, supporting the position that the guideline be lowered since the biological threshold of behavioural effects may be comparable with the TLV.